Survey of sand flies and Leishmania infection in Doi Saket District, Chiang Mai Province, Thailand - Sor-suwan, Sriwatapron; Jariyapan, Narissara; Mano, Chonlada; Somboon, Pradya (Biomedical Sciences and Clinical Medicine, 2017)
Objectives To survey sand flies in areas near the residence of a leishmaniasis patient’s home in Doi Saket District, Chiang Mai Province, Thailand and examine the Leishmania DNA. Methods Sand flies were collected using CDC light traps for two consecutive nights between 6 PM and 6 AM from February through September 2016. The study areas included rice fields, banana trees, chicken coops, and stacks of firewood. The Leishmania DNA was examined using a PCR method. Results A total of 863 adult sand flies were collected. Among the 425 females, five species were morphologically identi fied, i.e., Phlebotomus stantoni, Sergentomyia gemmea, S. barraudi, S. indica, and S. hivernus. Sergentomyia indica was the predominant species. Most of the flies were collected from chicken coops. The highest density of sand flies captured was in May with an average temperature of about 29 ºC and relative humidity of approximately 61%. No Leishmania DNA was detected in any of the sand flies collected in this study. Conclusions This study provided information on the different distribution patterns of sand fly species in Doi Saket District, Chiang Mai Province, Thailand where the leishmaniasis case was located. No Leishmania DNA was detected in the sand flies collected in this study. Further study is required to better understand the vector status of sand flies in Thailand.